Aristotelian rhetoric, pluralism, and public administration - Molina, Anthony Deforest; Spicer, Michael W. (2004)
This article discuss how Aristotle's thought on rhetoric can help public administrators deal with situations that involve conflicting and irreconcilable values. We argue that Aristolelian rhetoric can be helpful to public administrators in dealing with value conflicts, because it promotes a greater self-consciousness among administrators about their own values, encourages them to seek ways of accommodating their values to the values of others, discourages any sense of finality in resolving value conflicts, and requires that administrators take account of the concrete specifics of particular practical situations in dealing with value conflicts. - Reproduced.
Keywords: Public administration